2015
DOI: 10.2174/1389557515666150227105415
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine Kinases Signalling in Carcinogenesis

Abstract: Sphingosine kinases (Sphk1 and 2) regulate the prodution of sphingosine-1-phosphate (S1P), that is key molecule in cancer development. SphK1, which is commonly overexpressed in malignant tumours, significantly contributes to the pathogenesis of various types of cancer as well as to resistance to different Tyrosine Kinase inibitors (TKIs). Even, SphK2 may promote apoptosis and inhibit cell growth but its role has not yet been fully understood in pathologic conditions. Different growth factorsinduced activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 0 publications
3
19
0
Order By: Relevance
“…We further showed that TRPC1‐mediated Ca 2+ entry was required to induce basal SPHK1 activity and S1P generation because expression of a pore‐deleted TRPC1 mutant increased SPHK1 promoter activity, SPHK1 expression, and S1P levels. We also showed that SK1‐I, a specific inhibitor of SPHK1 (41, 5658), was comparatively less effective in disrupting basal barrier function in TRPC1‐null ECs, especially at 20 μM, supporting the central concept that loss of TRPC1 augments basal SPHK1 expression and thereby increases AJs integrity. The question arose that preexisting S1P should be able to ligate S1PR1 and protect against barrier dysfunction even though no new S1P was being made as a result of inhibition of SPHK1 by SK1‐I.…”
Section: Discussionsupporting
confidence: 60%
“…We further showed that TRPC1‐mediated Ca 2+ entry was required to induce basal SPHK1 activity and S1P generation because expression of a pore‐deleted TRPC1 mutant increased SPHK1 promoter activity, SPHK1 expression, and S1P levels. We also showed that SK1‐I, a specific inhibitor of SPHK1 (41, 5658), was comparatively less effective in disrupting basal barrier function in TRPC1‐null ECs, especially at 20 μM, supporting the central concept that loss of TRPC1 augments basal SPHK1 expression and thereby increases AJs integrity. The question arose that preexisting S1P should be able to ligate S1PR1 and protect against barrier dysfunction even though no new S1P was being made as a result of inhibition of SPHK1 by SK1‐I.…”
Section: Discussionsupporting
confidence: 60%
“…The SphKs family includes two distinct isoforms of SphK1 and SphK2, of which SphK1 is the predominant form in the lung, kidney, blood, and spleen [13]. Studies have shown that SphK1/S1P axis plays a crucial role in tumorigenesis, hormonal therapy and chemotherapy resistance [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mammals encode two SK isozymes (SK1 and SK2) that have different subcellular localizations, functions and pharmacology (3, 6, 7). For example, overexpression of SK1 is oncogenic (8, 9), while transfection with SK2 was originally reported to inhibit cell growth and to induce apoptosis (10).…”
Section: Introductionmentioning
confidence: 99%